A systematic integrative review examining the impact of Australian rural and remote maternity unit closures. (December 2021) - Bradow, Jeannine; Smith, Sally De-Vitry; Davis, Deborah; Atchan, Marjorie
Abstract: Background: Rural and remote Australian women are less able to access locally situated maternity care and birthing facilities, largely due to the gradual closures of rural and remote birthing services. Closures have occurred due to workforce issues, safety and quality issues and economic rationalisation of services to offset rising health system costs. An examination of the published literature to gain a deeper understanding of this phenomenon is warranted. Question: What are the impacts of rural and remote maternity unit closures in Australia? Methods: A systematic integrative review of published literature on Australian maternity unit closures was undertaken using Whittemore and Knafl's (2005) framework. A database search was conducted with date limiters of 2010 to 2020 on papers within the search parameters "maternity unit*" AND closure* AND women AND (midwife OR midwives) AND Australia, also with "birth unit", "labour ward" and "rural" in varying combinations. This search resulted in 348 papers. After applying the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) process and the Crowe Critical Appraisal Tool (CCAT) and discarding those non-relevant, seven papers remained. Findings: A methodological analysis of seven papers occurred, three qualitative studies, three quantitative studies and one mixed methods study. Two main stakeholders were identified, the woman, and the health service. Women identified risks associated with travel, lack of access to services, costs or financial issues, safety, and emotional burdens. Women explicitly stated that access to local maternity services would negate many of their concerns. Health services indicated closures were due to safety and quality considerations and workforce issues. Conclusion: Conflict exists in trying to meet the perceived needs of both stakeholder groups. Published evidence supports midwifery models for low-risk women. National policy also supports woman-centred care; however, local service uptake is minimal due to organisational barriers.